2006
DOI: 10.1200/jco.2005.05.1037
|View full text |Cite
|
Sign up to set email alerts
|

Late Cardiac Mortality and Morbidity in Early-Stage Breast Cancer Patients After Breast-Conservation Treatment

Abstract: Irradiation to the left breast is not associated with a higher risk of cardiac death up to 20 years after treatment, but is associated with an increased rate of diagnoses of coronary artery disease and myocardial infarction compared with right breast treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
209
1
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 369 publications
(233 citation statements)
references
References 37 publications
15
209
1
5
Order By: Relevance
“…[21][22][23][24] However, the published literature concerning late cardiopulmonary mortality in patients with esophageal cancer who are treated with RT is scarce. Morota et al investigated 74 patients who were treated with definitive concurrent CRT using an extended field from the supraclavicular fossa to the gastroesophageal junction, and concluded that the risk of grade 3 or greater cardiopulmonary toxicities was greater in patients aged > 75 years (29% vs 3%).…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24] However, the published literature concerning late cardiopulmonary mortality in patients with esophageal cancer who are treated with RT is scarce. Morota et al investigated 74 patients who were treated with definitive concurrent CRT using an extended field from the supraclavicular fossa to the gastroesophageal junction, and concluded that the risk of grade 3 or greater cardiopulmonary toxicities was greater in patients aged > 75 years (29% vs 3%).…”
Section: Discussionmentioning
confidence: 99%
“…18,19 The role of radiation directed to the internal mammary nodes was questioned, particularly since its use was associated with radiation-associated cardiac death, which was probably attributable to outdated radiation techniques. [20][21][22][23][24][25][26][27][28][29] It remains undefined whether this risk is significantly lowered by advances in radiation techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Trials have shown an increase in cardiac mortality and morbidity, and a relationship between higher absorbed radiation dose and a higher incidence of ischemic heart disease (IHD) [5][6][7]. In some studies, RT to the left breast is associated with higher risk of IHD than RT to the right breast, probably due to the localization of the heart [8,9]. Dosimetry studies have shown that the left anterior descending artery (LAD) receives the highest radiation doses [10,11] and a higher incidence of coronary artery stenosis in the LAD has also been shown after RT of left-sided BC [12,13].…”
Section: Introductionmentioning
confidence: 99%